Fish Fauna of Kankai River of Jhapa District, Eastern Nepal - Acharya, Umesh; Shrestha, Om Hari; Acharya, Geeta Sharma; Thapa, Rakshya; Tamang, Sagar (Amrit Research Journal, 2021)
This study explored ﬁsh diversity in the Kankai River of the Jhapa district. Fishes were collected by cast net (mesh 0.5cm) from three sampling sites: Domukha, Kotihom and Bengdada in rainy and winter seasons. Water temperature, pH and water velocity were recorded at each site. A total of 20 ﬁsh species belonging to 4 orders and eight families were recorded. Cypriniformes has recorded as the dominant order with 16 species, followed by Siluriformes with two species and Perciformes, and Synbranchiformes with a single species each. The value of Shannon’s diversity Index (H’) was higher in winter (3.06; Domukha) than a rainy season (1.06; Bengdada), indicating higher diversity in winter than rainy season. Only a slight variation in pH was recorded during the study period, i.e. 7.9 (highest) and 7.8 (lowest). The highest and the lowest temperatures recorded in the rainy season were 280C and 270C, and that of winter were 170C and 150C. The highest and the lowest water current recorded in the rainy season were 0.75 m/s and 0.68 m/s, and that of winter were 0.55 m/s and 0.52 m/s. It should be noted that to have comprehensive ﬁsh diversity status, future investigation covering more seasons and more sampling sites is essential.